2022
DOI: 10.1159/000525584
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Anterior Scleral Thickness, Corneal Biomechanical Response, and Ocular Parameters

Abstract: Purpose: to assess anterior scleral thickness (AST) across diverse scleral meridians and to evaluate the relationship with corneal biomechanical response and several ocular parameters. Methods: This prospective non-randomized study comprised 50 eyes of 50 patients (mean age, 29.02 ± 9.48 years). Anterior scleral thickness was measured meridionally at three scleral locations (1, 2, and 3 mm posterior to the scleral spur) using swept-source optical coherence tomography. A multivariate model was created to associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Previous studies examining factors affecting the ST reported a relationship between the CCT and the anterior ST in healthy eyes. 13,14 In the current study, there was a significant correlation between the ST and the CCT. In addition, a significant correlation was found between the ST and the minimum corneal thickness in the keratoconus group.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies examining factors affecting the ST reported a relationship between the CCT and the anterior ST in healthy eyes. 13,14 In the current study, there was a significant correlation between the ST and the CCT. In addition, a significant correlation was found between the ST and the minimum corneal thickness in the keratoconus group.…”
Section: Discussionsupporting
confidence: 51%
“…The session was scheduled the same day in the afternoon between 3:00 p.m. and 7:00 p.m. to minimize the confounding effects of diurnal variations in AST [19]. Scleral imaging and scleral data analysis were carried out using the method previously described by Burguera-Giménez et al [28]; however, a short summary is described below.…”
Section: Methodsmentioning
confidence: 99%

Anterior Scleral Thickness Profile in Keratoconus

Burguera-Giménez,
Díez-Ajenjo,
Burguera
et al. 2023
Life
Self Cite